Role of physical activity in GLP-1 receptor agonist therapy for obesity treatment - Zdziebkowski, Łukasz; Wilska, Hanna; Szatkowska, Dorota; Ziętara, Dominika; Kmieć, Kacper; Topolska, Aleksandra; Komorowski, Marcin; Janiszewski, Michał; Surosz, Natalia; Grochowalski, Michał; et al. (Quality in Sport, 2025)
Introduction: WHO recognized it as a global obesity crisis. Globally there are 2,5 billion adult people living with excess body weight (43% of global adult population). Out of these 890 million have obesity disease (16% of global adult population). This forces to implement safe and effective body mass reduction treatment. Materials and methods: The PubMed database has been sardch to perform a literature review that was conducted for scientific purposes focused on high quality studies like randomized trials, meta-analyses, observational cohorts published during the last 5 years (from 2020). Results: Due to glucagon-like peptide 1 receptor antagonist (GLP-1 RA) pharmacological treatment of obesity became very popular. GLP-1 RAs can induce large initial weight losses. Although a healthy diet and regular physical activity usually lead to 3% to 5% of their body weight reduction they are crucial parts of managing weight. Compilation of GLP-1 RA pharmacotherapy with regular exercises leads to higher effectiveness of body mass reduction with lower reduction of lean body mass. It also makes weight reduction more durable with better metabolic outcomes like enhancing muscle glucose usage and lowering inflammation level. Exercises also contribute to improving general fitness, muscle mass and improvement of cardiovascular condition which improves quality of life of people with obesity disease. The aim of this study is to assess the role of physical activity in a process of weight reduction with use of GLP-1 RA. Conclusion: Physical activity is complemented with GLP-1 RA as obesity treatment. An intervention of combined pharmacological and lifestyle approach appears to offer the best long-term obesity management. Keywords: GLP-1 receptor agonist, obesity treatment, liraglutide, semaglutide, tirzepatide, weight loss, physical activity, lifestyle interventions